Effects of implementing the Alexander technique on enjoying the sense of motherhood in the postpartum period - Somayeh Banoofatemeh; Hamid Reza Oreyzi; Parvin Bahadoran (Wolters Kluwer Medknow Publications, 2017)
Background: The broad concept of maternal well-being includes psychological concepts, social aspects, and aspects of becoming a mother. The present study aimed to investigate the effects of implementing the Alexander technique on enjoying the sense of motherhood. Materials and Methods: This study was a clinical trial conducted in two phases. In the first phase, using the exploratory and confirmatory factor analysis, 226 mothers were asked to undergo a scale test of enjoying the sense of motherhood after childbirth. In the second phase, 88 pregnant women were divided into two experimental groups. The data collection tool was a researcher-made questionnaire about enjoying the sense of motherhood. Independent samples t-test, Mann-Whitney test, Chi-square test, Fisher's exact test, analysis of variance test, Box test, and Levine test were used to analyze the data. Results: Results of this study showed that the mean scores of the constructs of enjoying pregnancy (P > 0.001), motherhood, and child care satisfaction (P > 0.001) in the experimental group were significantly higher than the control group. Moreover, the construct of trusting their own abilities to cope with maternal duties (P > 0.01) did not show significant differences between the two groups. Conclusions: The findings indicated that the Alexander technique can promote mothers' psychological well-being and their pleasure of becoming a mother and the related constructs. Results also revealed that using this technique, educating and recommending pregnant women to use this technique will be beneficial.